KREASI NANAS SEBAGAI MOTIF PADA KAIN PANJANG - Nurika Chairani; Widdiyanti Widdiyanti; Wisnu Prastawa (Institut Seni Indonesia Padangpanjang, 2021)
Pineapple has an elliptical and ovoid shape. The shape of this pineapple is used as a creative motif on a Long cloth. The method of creating works through three stages, namely exploration, design, and embodiment. The exploration stage is looking for direct reference ideas or literature studies, the design stage is pouring ideas into several sketches and then becoming the chosen design, the realization stage is realizing the selected design into work with the batik tulis technique. The form of the work that is realized is a Long cloth with batik tulis technique as many as 3 works and 4 designs. The first work is entitled